The response of foraminifera to rapid sea-level rise from tidal restoration of Ni-les'tun marsh, Oregon, U.S.A - Milker, Yvonne (2023)
Foraminifera preserved in saltmarshes are widely used to reconstruct relative sea-level change (RSL), and inferred from this, coseismic vertical coastal motions following an earthquake. However, how quickly foraminifera respond to rapid changes in RSL is poorly understood. Here, we present a six-year foraminiferal study of the tidal restoration of Ni-les'tun marsh and a comparison of modern and fossil assemblages. We installed eight stations on the marsh and sampled these stations for live foraminifera prior to and during the first six years after tidal restoration (2011–2017), and we extruded one short core at station 1 in 2016. At stations 1 to 7, tidal flat/low marsh assemblages, dominated by Miliammina fusca, colonized 10 months to 2.5 years after tidal restoration. At station 8, the first living mixed assemblage of foraminifera, dominated by Haplophragmoides wilberti, was found 2 years after tidal restoration. Our observations suggest that M. fusca, and to some extent H. wilberti, are opportunistic species (r-strategists), able to increase their standing crop rapidly after invading a new habitat (to up to ~3600 specimens per 10 cm3 sediment volume). Potential causes for the delay in foraminifera colonization include their reproductive cycle and/or limited food availability due to the slow response of the vegetation community and soil development to tidal restoration. However, the similarity among assemblages and concentrations of agglutinated foraminifera between the fossil and modern sediments, indicate that post-depositional taphonomic processes have minimal influence when incorporated in the stratigraphic record. Although foraminifera have shown a delayed response to tidal restoration in the Ni-les'tun marsh, the similarities between the modern and fossil assemblages indicate that the delayed response of foraminifera to tidal restoration is undetectable in study areas with low sedimentation rates (in this case 3.3 mm/yr) after tidal restoration. In the case of high post-earthquake sedimentation rates, sampling a few cm higher rather than immediately above an earthquake contact could avoid uncertainties of coseismic vertical motions when foraminifera have a delayed colonization.